1981
DOI: 10.1021/bi00504a022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of urocanase as studied by deuterium isotope effects and labeling patterns

Abstract: Nicotinamide adenine dinucleotide (NAD) dependent urocanase (4'-imidazolone-5'-propionate hydro-lyase, EC 4.2.1.49) from Pseudomonas putida was found to catalyze an exchange reaction between solvent and the 4'-hydrogen of urocanate or imidazolepropionate at a rate faster than that of overall deuterium was compared to unlabeled urocanate as a substrate, no isotope rate effect was noted. For examination of the possibility of an NAD+-mediated intramolecular hydride transfer of the 4'-hydrogen to a position on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The isolation and characterization of a covalent adduct between the NAD from urocanase and imidazolepropionate support a chemistry for this reaction distinct from that for an NADH-mediated transfer of a hydride ion. While novel mechanisms for urocanase catalysis have been previously proposed in which the coenzyme acts as an electrophile, forming a covalent addition complex with the substrate to facilitate electron delocalization (Egan et al, 1981;Keul et al, 1979), the present report constitutes the first direct support for such a possibility. Our results, although derived from the study of a substrate analogue rather than the actual substrate, would seem relevant to the events occurring on the enzyme upon binding urocanate since recent reports indicate that urocanase catalyzes a solvent exchange of the 5 hydrogen of both imidazolepropionate and urocanate (Egan et al, 1981; Gerlinger & Retey, 1980).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The isolation and characterization of a covalent adduct between the NAD from urocanase and imidazolepropionate support a chemistry for this reaction distinct from that for an NADH-mediated transfer of a hydride ion. While novel mechanisms for urocanase catalysis have been previously proposed in which the coenzyme acts as an electrophile, forming a covalent addition complex with the substrate to facilitate electron delocalization (Egan et al, 1981;Keul et al, 1979), the present report constitutes the first direct support for such a possibility. Our results, although derived from the study of a substrate analogue rather than the actual substrate, would seem relevant to the events occurring on the enzyme upon binding urocanate since recent reports indicate that urocanase catalyzes a solvent exchange of the 5 hydrogen of both imidazolepropionate and urocanate (Egan et al, 1981; Gerlinger & Retey, 1980).…”
Section: Discussionmentioning
confidence: 52%
“…While novel mechanisms for urocanase catalysis have been previously proposed in which the coenzyme acts as an electrophile, forming a covalent addition complex with the substrate to facilitate electron delocalization (Egan et al, 1981;Keul et al, 1979), the present report constitutes the first direct support for such a possibility. Our results, although derived from the study of a substrate analogue rather than the actual substrate, would seem relevant to the events occurring on the enzyme upon binding urocanate since recent reports indicate that urocanase catalyzes a solvent exchange of the 5 hydrogen of both imidazolepropionate and urocanate (Egan et al, 1981; Gerlinger & Retey, 1980). In addition, the following paper (Matherly et al, 1982) presents kinetic evidence for the existence of a reaction intermediate involving NAD and urocanate or imidazolepropionate.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The dependence of the catalytic activity of Pseudomonas putida urocanase on added NAD+ has been demonstrated previously (16). The mechanism of this unique enzymatic reaction is not yet clear, but a new proposal for the role of NAD+ was offered by Egan et al (3). Urocanase from P. putida is almost completely inactivated in cold, starved cells (9) and partially inactivated in commercially or laboratory-grown cells (12).…”
mentioning
confidence: 94%
“…The mechanism for the urocanase-catalyzed conversion of urocanic acid to 5-hydroxyimidazolepropionic acid, the enol form of oxoimidazolepropionic acid, has been the focus of a number of studies aimed at understanding the role of NAD+ (nicotinamide adenine dinucleotide) in the reaction process. While urocanase (EC 4.2.1.49) has an absolute catalytic requirement for a tightly bound NAD+ (Egan & Phillips, 1977;Keul et al, 1979), NADH (reduced NAD) is apparently not formed during catalysis, as shown by the absence of a direct transfer of a hydride ion in deuterium labeling experiments (Egan et al, 1981) and by the demonstration that the enol tautomer of oxoimidazolepropionic acid is the reaction product (Kaeppeli & Retey, 1971; .…”
mentioning
confidence: 99%